A multi-centre analysis of radiotherapy beam output measurement. (October 2017) - Bolt, Matthew A.; Clark, Catharine H.; Chen, Tao; Nisbet, Andrew
Abstract: Background and purpose: Radiotherapy requires tight control of the delivered dose. This should include the variation in beam output as this may directly affect treatment outcomes. This work provides results from a multi-centre analysis of routine beam output measurements. Materials and methods: A request for 6MV beam output data was submitted to all radiotherapy centres in the UK, covering the period January 2015–July 2015. An analysis of the received data was performed, grouping the data by manufacturer, machine age, and recording method to quantify any observed differences. Trends in beam output drift over time were assessed as well as inter-centre variability. Annual trends were calculated by linear extrapolation of the fitted data. Results: Data was received from 204 treatment machines across 52 centres. Results were normally distributed with mean of 0.0% (percentage deviation from initial calibration) and a 0.8% standard deviation, with 98.1% of results within ±2%. There were eight centres relying solely on paper records. Annual trends varied greatly between machines with a mean drift of  +0.9%/year with 95th percentiles of +5.1%/year and −2.2%/year. For the machines of known age 25% were over ten years old, however there was no significant differences observed with machine age. Conclusions: Machine beam output measurements were largely within ±2% of 1.00 cGy/MU. Clear trends in measured output over time were seen, with some machines having large drifts which would result in additional burden to maintain within acceptable tolerances. This work may act as a baseline for future comparison of beam output measurements.